Polsko-ukraińskie rokowania rozejmowe w czerwcu 1919 roku - Legieć, Jacek (Acta Universitatis Lodziensis. Folia Historica, 1999)
This article attempts to explain the circumstances, the course and the results of the truce talks aiming at finishing the Polish-Ukrainian war. Those talks were the results of the policy of the leaders of both nations - Józef Piłsudski and Symon Petlura, who tried to close the conflict and to conclude a Polish-Ukrainian antibolshevic alliance. Both sides met in Lvov on June 7th and as the result of that meeting they signed the armistice on June 16th which, according to their hopes, should have become an entrance to the further talks about the alliance. Unfortunately the agreement was torpedoed by the leaders of the Ukrainians from Galicia, whose army was in that time in offensive against the Polish troops. Due to that fact the truce talks failed for the time being. The very signation of the agreement was however not an effect of the success of the Ukrainian army, but a part of a wider Polish political plan. In spite of the failure of that attempt the Polish-Ukrainian talks were continued and the conflict never broke back in the similar scale.